Long-term exposure to phenanthrene at environmental-level induces intestinal dysbiosis and disrupted hepatic lipid metabolism in mice. (1st January 2021) - Yu, Xiu; Lv, Kongpeng; Guan, Shuyuan; Zhang, Xinyun; Sun, Lingbin
Abstract: Phenanthrene (Phe), among the most ubiquitous polycyclic aromatic hydrocarbons (PAHs) existing in nature and foodstuffs, has severe effects on hepatic lipids metabolism. However, the detailed mechanism involved is still unknown. For environmental chemicals can disturb intestinal microbiota, which plays a vital role in lipids metabolism, we hypothesized that oral exposure to Phe may disrupt the intestinal microbiota, leading to the induction of an abnormal inflammatory response and lipid metabolism dysfunction. Herein, male mice were orally exposed to Phe (0.05, 0.5 and 5 mg/kg/2d) for ten weeks and the results showed that long term exposure to Phe induced significant alteration in relative Bacteroidetes, Firmicutes and Proteobacteria abundance in male mice. Histopathological anomalies, and significantly increased hepatic levels of free fatty acid, cholesterol and triglyceride were observed as well. The expression of hepatic proteins linked to lipid metabolism including peroxisome proliferator-activated receptors (PPARs), liver X receptor β (LXRβ) and retinoid X receptors (RXRs) were upregulated. The importance of the gut microbiota in Phe-altered lipid metabolism disorder was further confirmed by fecal microbiota transplantation (FMT). FMT intervention boosted microbial diversity and attenuated Phe-induced elevation in liver somatic index and hepatic total lipids levels. These results demonstrated that environmental-level Phe altered the composition of gastrointestinal bacteria and subsequently induced hepatic lipid metabolism disorder. These results would be helpful for understanding the health risk posed by Phe. Graphical abstract: Summary of the possible mechanism underlying the influence of Phe exposure on gut microbiota dysbiosis in mice. Image 1 Highlights: Phe exposure increased body weight, liver weight and lipid content in male mice. Intragastric administration of Phe induced gut microbiota dysbiosis in male mice. Phe-induced microbiota dysbiosis disturbed lipid metabolism. Gut microbiota diversity improved after fecal microbiota transplantation.